An analysis of accounts of emotional and motivational states in the development of a clinical case. (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
The study aimed to identify the existence of a relationship between references to feelings, emotions or motivational states (SEM) in verbal interaction between therapist and client and the evolution of the complaints or problems which the client reported. A clinical case was monitored over the course of a year, in which the verbalizations of a behavior-analytic therapist and a client were analyzed. In order to investigate the development of the therapy, indicators of complaint or perception of change were designed. The references to SEM were compared both inside and outside of the emotional episodes, defined as sequences of dialogue between therapist and client in which there was at least one reference to the client’s SEM. It was found that the client’s main problems were her marital relationship and her lack of assertiveness. However, the evolution of these problems, as well as the other complaints, did not always occur regularly or in a positive fashion. There was also no consistent relationship between a particular type of complaint and the report of a specific SEM. On the other hand, it was confirmed that the behavior-analytic therapists did not accord special importance to public behavior to the detriment of private behavior, and thus dealt with the SEM in a similar way to any other behavior. Finally, methodological problems, which were common to the investigation of private events in the therapeutic context, were discussed. Some changes were also suggested in order to improve the method used herein and which could be useful in future investigations.
Keywords: Private events; Behavior-analytic therapy; Feelings; Emotions